ANALISIS RESEPSI GEN Z PEREMPUAN SURABAYA TERHADAP PENJUALAN PRODUK PAKAIAN MUSLIM DI LIVE TIKTOK SHOP - Salsabilah, Yazz Daniar Izzah; Sukardani, Puspita Sari (Universitas Negeri Surabaya, 2024)
Currently, social media has various functions, one of its functions is to help in the world of buying and selling, the social media chosen in this study is the TikTok Shop social media platform with its live shopping features. How does the audience view the live tiktok shop with the sale of Muslim clothing products in it. This research is qualitative research using Stuart Hall's reception theory. This theory explains how a media broadcast can influence its audience so that it can be categorized into three parts, Dominance, Negotiation and Opposition. Data collection techniques were carried out by means of interviews and in-depth observation. The selected audience is generation Z women in Surabaya, how the audience accepts and interprets the broadcast of the live tiktok shop with the sale of Muslim clothing products in it, the result is that there are audiences who agree and accept well as a whole, there are audiences who accept but with consideration, and there are audiences who disagree and do not accept well the existence of a live tiktok shop with the sale of Muslim clothing.